A clinical case of a complicated course of influenza A/H3N2 strain in the epidemiological season 2017-2018. - A. V. Chernilovsky; S. V. Boltyansky; V. A. Peshkova (Medičnì Perspektivi)
The article presents information on the course of influenza of H3N2 strain in a man aged 48 years, with complications in the late post-infectious period. A number of risk factors that led to this outcome of the disease are disclosed.